5 - Dé-mondialiser le secteur minier pour développer l’Afrique - Kasongo, Emmanuel Mungongo (Africa Development, 2021)
The term “de-globalization” developed by Walden Bello, largely used by Arnault de Montourg as a theme of the presidential campaign in France, did not seem to be widely echoed in the academic world, yet, it is about the recovery of the French economy that he envisaged. Multinational or transnational corporations have been part of the economic landscape for many decades, but the current global economic order, which favors trade liberalization and the globalization of the economy, and increasingly considers host countries as places of extraction of raw materials while the processing and all the benefits associated with the exploitation of mineral resources serve the countries of origin. In a common sense, de-globalization is a concept advocating a new organization of the world economy. It takes account of the increase in human interdependence in the world but strives to shield them from the domination of financial globalization and free trade. It aims to make the world’s economic organization fairer, more social and ecological through new rules containing the negative effects of free trade and neo-liberalism. It also seeks better articulation of decisions taken in the civic framework with actions at the international level (http://fr.wikipedia. org/wiki, Kinshasa, le 13: 2014). We consider “de-globalization” in a much more nuanced sense to evoke the deconstruction of the economic cycle of mineral exploitation in Africa in general and particularly in the DRC. It is not about combating globalization which, by its nature, is characterized by the intensification of international trade and the emergence of a global financial sphere. It is necessary to criticize globalization in relation to its secular effects in countries of mineral resource extraction. This is all the more difficult when it is a country where the structure has long been analyzed from the image of a trinity made up of the Administration, Church and large corporations (Crawford Young 1965:12).